Katalis Asam Padat Berbasis Karbon Kulit Ubi Kayu Tersulfonasi Untuk Produksi Biodiesel Dari Minyak Sawit - Fadli, Muhammad Al (RC-INSTITUT, 2019)
Palm oil is one of the vegetable oils that can be used as diesel fuel (biodiesel) through a transesterification reaction with alcohol assisted in the form of a solid acid catalyst (activated carbon). Solid acid catalyst can be made from cassava skin carbon by being hydrolyzed to produce carbon at 250 oC. Next the carbon is sulfonated chemically with 98% H2SO4 solution. In this research, biodiesel was made through a transesterification reaction between bimoli and methanol oil with a ratio of 6: 1, and using a catalyst with sulfonation variation of 2 hours, 4 hours, 6 hours, and 8 hours. The reaction lasts 65 oC and takes 2 hours. The properties of solid acid catalysts were identified using FTIR and XRD. The results of FTIR spectra characterization show that at wave number 1100-1200 cm-1 there is a group O = S = O which is covalently bonded with the carbon structure in each sample of SCCP. The results of the maximum percentage of sulfonate fraction are located at 6 hours of sulfonation time using XRF. The results of biodiesel obtained were tested for physical properties such as density, flow rate and acid number. Keywords—Solid acid catalyst, cassava peel, sulfonated carbon, biodiesel.